2012
DOI: 10.1002/jps.22737
|View full text |Cite
|
Sign up to set email alerts
|

An Adsorption Chromatography Assay to Probe Bulk Particle Transport Through Hydrogels

Abstract: Biopolymer-based hydrogels such as mucus and the basal lamina play a key role in biology where they control the exchange of material between different compartments. They also pose a barrier that needs to be overcome for successful drug delivery. Characterizing the permeability properties of such hydrogels is mandatory for the development of suitable drug delivery vectors and pharmaceutics. Here, we present an experimental method to measure bulk particle transport through hydrogels. We validate our assay by app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
1
5
1
Order By: Relevance
“…In the case of positively charged CTAB-PCL NPs, increasing the pH may result in higher attraction with mucin chains thus rendering those particles more adhesive, and thus more hindered. Contrasting with our results for CTAB-PCL NPs, Ribbeck and colleagues , using MPT observed that not only negatively charged microparticles but also positively charged microparticles presented higher mobility in reconstituted porcine purified gastric mucin when increasing pH from 3 to 7. These contrasting observations may be explained by possible differences in the structure of reconstituted porcine purified gastric mucin with changing pH values, by the low concentration of mucin used (0.25–1%), or simply by the large size of utilized particles (around 1 μm).…”
Section: Resultscontrasting
confidence: 99%
“…In the case of positively charged CTAB-PCL NPs, increasing the pH may result in higher attraction with mucin chains thus rendering those particles more adhesive, and thus more hindered. Contrasting with our results for CTAB-PCL NPs, Ribbeck and colleagues , using MPT observed that not only negatively charged microparticles but also positively charged microparticles presented higher mobility in reconstituted porcine purified gastric mucin when increasing pH from 3 to 7. These contrasting observations may be explained by possible differences in the structure of reconstituted porcine purified gastric mucin with changing pH values, by the low concentration of mucin used (0.25–1%), or simply by the large size of utilized particles (around 1 μm).…”
Section: Resultscontrasting
confidence: 99%
“…This agrees with previous findings on particle diffusion and particle translocation experiments in reconstituted mucin solutions 23, 30 and underlines the possibility to tune the permeability of this biopolymer based diffusion barrier by pH. We emphasize that our single particle tracking assay might still underestimate the virus trapping effect established by mucins: the residual mobility observed for HPV viruses in mucin solutions could represent thermal undulations of the mucin biopolymers to which the virus particles are bound, rather than a true local diffusion of the virus particles.…”
Section: Discussionsupporting
confidence: 94%
“…The complex filtering behavior can be traced back to two main effects, namely, the structure and pore size of the polymeric network, as well as mucin-particle interactions (1,3,(5)(6)(7). Previous studies have verified that penetration of mucin gels may be enhanced by the addition of mucolytic agents (8)(9)(10)(11), and it has been shown that the presence of degrading enzymes in the medium can enhance the transport of particles in other hydrogels as well (12). However, complete degradation of the mucus is generally not desirable because of the gel's important protective function and the resulting need to preserve the integrity of the mucosa (5).…”
Section: Introductionmentioning
confidence: 99%